A study of wastewater treatment conditions for the poultry meat processing enterprise - Makhlay, Konstantyn; Tseitlin, Musii; Raiko, Valentina (Eastern-European Journal of Enterprise Technologies, 2018)
For the local treatment of wastewater of food industry enterprises, physicochemical treatment methods are widely used, which, with properly selected reagents and their doses, allow achieving high treatment efficiency. At the same time, doses of reagents and conditions for their use can differ sharply between enterprises, therefore the regularities of the treatment process must be studied at a particular drain. In the paper, the regularities of the process of wastewater coagulation by coagulants and flocculants of different chemical composition are examined on the example of the wastewater of the turkey meat processing enterprise. The regularities of the process of wastewater coagulation in a wide range of pH values of the medium are studied. It is experimentally determined that the optimum pH of the medium for the use of polyaluminum chloride is in the range 5.9÷6.4, iron chloride 6.2÷6.7, iron sulfate 5.1÷5.7. The regularities of the effect of the coagulant dose on the efficiency of suspended solids removal from wastewater and color reduction are established. Based on the data obtained, the most optimum doses of coagulants are determined. The rational dose of polyaluminum chloride was 140 mg/l, iron sulfate – 110 mg/l and iron chloride – 80 mg/l. The regularities of the process of wastewater flocculation with the use of flocculants of different charges and molecular weight are investigated. The most effective types of flocculants are determined, and optimum reagent doses are established. The rational conditions for physicochemical wastewater treatment using coagulants and flocculants are determined. The obtained data make it possible to optimize the operation of local treatment facilities of the poultry processing enterprise: to increase performance, as well as to reduce operating costs. The selected binary combinations of reagents allow achieving the efficiency of suspended solids removal of 99.4 % and color reduction – 82.4 %.